Enhanced energy conversion efficiency promoted by cavitation in gasoline direct injection. (15th February 2023) - Zhang, Qing; Gao, Ya; Chu, Miaoqi; Chen, Pice; Zhang, Qingteng; Wang, Jin
Abstract: High-pressure direct fuel injection plays the most crucial role in energy conversion and improving engine combustion efficiency and emission. The optimization of turbulent and multiphase fuel injection has focused on controlling hydrodynamic parameters such as injection pressure. While the thermodynamic influence is often considered in the flash boiling situation, we inquire into how gasoline-type fuel's hydro- and thermodynamic properties impact the injection dynamics by fuel-temperature-induced cavitation. The turbulent and cavitating flows emanating from the direct-injection nozzle are visualized by ultrafast x-ray imaging with an unprecedented spatiotemporal resolution. The ultrafast liquid-fuel dynamics are dominated by injection pressure as well as fuel temperature through cavitation, an important thermodynamic parameter but often difficult to control in engine combustion. With the most direct and quantitative measurement, we discovered that the near-nozzle fuel-jet dynamics could be perfectly scaled by a single dimensionless parameter, cavitation number, particularly sensitive to the fuel temperature, in a wide operation range. This universal scaling shows that cavitation can be harnessed to elevate the pneumatic-hydraulic to kinetic energy conversion efficiency, which is critical for promoting fuel atomization and engine combustion performance. This enhancement effect will have even more impact on engine combustion using alternative low-emission fuels with higher saturated vapor pressure. Highlights: Cavitation is harnessed to promote energy conversion efficiency in fuel injection. Fuel dynamics is scaled by cavitation number, interplay of temperature and pressure. More impact on alternative low-emission fuels with higher saturated vapor pressure. High resolution, precision, and quantitativeness enabled by ultrafast x-ray imaging. Revealed high-resolution (<1 m/s) dynamics of high-pressure direct-injection fuel jets.